Note on numerical and ponderous productivity of three purebred rabbits - García Hernández, Yoleisy; Ponce de León, Raquel (Cuban Journal of Agricultural Science, 2017)
A total of 3894 kindling records from 2014 and 2015 of California (C), Chinchilla (Ch) and New Zealand (N) breeds were used to determine numerical (NUMPROD) and ponderous (PONPROD) productivity per reproduction cage, in a rabbit genetic unit. For the statistical analysis, the MIXED procedure of the SAS was used with the fixed effects: breed (3types), weaning month and consecutive period of kindling, with 12 and 24 levels, respectively; and with the random the breeder cage nested within the breed. The California breed was the one with the highest annual productive potential, with a numerical productivity of 22 weaned young rabbits and 12 kg of young rabbits. The BLUPs from breeder cages by breeds were similar, but they constitute a useful working tool for making decisions for the purpose of improving productive efficiency. Key words: productivity, rabbit, prolificacy, efficiency, breed